Comparison of 2 jump tests used to assess anaerobic power and capacity in elite alpine ski racers - Patterson, C.; Raschner, C. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Jump tests are popular to assess anaerobic power and capacity in alpine ski racers. Our lab has shown that training can improve the loaded repeated jump test (LRJT) results (1) which may lead to improved performance. We have also shown that LRJT results are only minimally related to ski racing performance (2). Male racers perform the LRJT with 40% body weight on a barbell. Many racers have spine and knee problems and cannot perform the test. We have developed a new squat test (60ST) for anaerobic power and capacity in ski racers. It has only 6 body weight jumps and 60 squats. The aim of this study is to compare the results of the 2 tests in male ski racers. METHODS: 9 male ski racers (Austrian national team juniors and European Cup) were tested with the 60ST in 2018. The 60ST required 3 reference body weight jumps, then 60 squats with 70% body weight on a barbell (90° knee angle, 2 minutes duration) immediately followed by 3 jumps again. The single best relative power of the 3 post-squat jumps was then expressed as a percentage of the best reference jump power. Data from the last LRJT in 2017 was used. The LRJT consisted of 60 jumps (2.5 minutes) on force platforms with a loaded barbell (40% body weight). The mean relative power of the last 12 jumps (30 seconds) was expressed as a percentage of the reference jump power performed 5 minutes before the test. The percentage results of the two tests were then compared with a student`s t-test and a Pearson`s correlation. RESULTS: The mean reference relative power of the 60ST was 43.5 W/kg, and post mean relative power was 39.0 W/kg, or 89.6% (range 83.6 - 98.6%) of the reference. The mean reference relative power of the LRJT was 41.5 W/kg, and the mean relative power of the last 12 jumps was 34.0 W/kg, or 82.0% (range 62.8 - 90.0%) of the reference. The students t-test showed that the 2 tests were significantly different (p = 0.04), and there was no correlation between the tests (r = 0.02). CONCLUSION: The difference in reference jumps was probably due to load difference. The 60ST reference was done with body weight and the LRJT reference was with 40% body weight. The drop off in power in the LRJT was greater, again due to the heavier load. The 60ST also produced fatigue, but markedly less than the 60ST. The 60ST involves less stress on the spine and knees, with only 6 body weight jumps. However, the athlete must have healthy knees and good core stability to perform 60 squats with an additional load of 70% body weight. 2 Athletes had 60ST post jump values of 98% of their reference, perhaps indicating that the test is too "easy". Some ski racers have commented that the LRJT is a good reflection of the fatigue experienced in a giant slalom race. Skiing will never will adequately simulated in a lab setting, but work is being conducted to develop a test that is taxing and simulates the demands of ski racing.